2016
DOI: 10.1073/pnas.1601196113
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of the respiratory supercomplex factors in Saccharomyces cerevisiae

Abstract: The respiratory supercomplex factors (Rcf) 1 and 2 mediate supramolecular interactions between mitochondrial complexes III (ubiquinolcytochrome c reductase; cyt. bc 1 ) and IV (cytochrome c oxidase; CytcO). In addition, removal of these polypeptides results in decreased activity of CytcO, but not of cyt. bc 1 . In the present study, we have investigated the kinetics of ligand binding, the singleturnover reaction of CytcO with O 2 , and the linked cyt. bc 1 -CytcO quinol oxidation-oxygen-reduction activities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 57 publications
6
55
1
Order By: Relevance
“…This interaction is proposed to alter the enzymatic properties of the Cyt c O , but the effect is not understood at a molecular level. In a recent study, we showed that the removal of the Rcf1 protein results in two populations of Cyt c O: one that is inactive and one that is essentially fully active . However, in our earlier study, we could not point to the site that was inactivated by removal of Rcf1.…”
contrasting
confidence: 60%
“…This interaction is proposed to alter the enzymatic properties of the Cyt c O , but the effect is not understood at a molecular level. In a recent study, we showed that the removal of the Rcf1 protein results in two populations of Cyt c O: one that is inactive and one that is essentially fully active . However, in our earlier study, we could not point to the site that was inactivated by removal of Rcf1.…”
contrasting
confidence: 60%
“…As observed previously [26] and shown in Figure 4A, also with the mitochondrial membranes we observed a small (~10% at 445 nm) rapid component with a time constant of ~100 s (as well as a major kinetic component with a time constant of ~9 ms). This observation indicates that the altered structural state reflected by the faster CO recombination is present also in the native membranes, although at a lower relative concentration compared to that observed with the CytcO-SMA native nanodiscs.…”
Section: Ligand Binding To the Catalytic Sitesupporting
confidence: 89%
“…Thus, with the detergent-purified CytcO, the rapid component represents CO recombination to heme a 3 in a local structural environment that differs from that in the other two samples (SMA-extracted nanodiscs and native membranes, where the CytcO resides in a membrane). Results from an earlier study with mitochondria showed that a rapid component with a similar time constant of ~100 s and the same spectral features as in detergent-purified CytcO (absorbance decrease at 430 nm) was observed upon removal of the Rcf1 protein [26]. Also this observation indicates that the 100-s component observed with the detergent-purified CytcO reflects CO binding to a…”
Section: Ligand Binding To the Catalytic Sitementioning
confidence: 59%
See 1 more Smart Citation
“…in stoichiometrically equivalent amounts as other complex IV subunits), Rcf1 may exert an influence over substrate binding and the enzymatic properties of complex IV. Indeed, the binding of a Hig1 family member, HIGD1A, to the complex IV enzyme has been indicated to enhance the activity of the enzyme (33), and evidence to indicate altered cytochrome c binding properties to the complex IV enzyme is obtained in mitochondria lacking the Rcf1 protein (15).…”
Section: Discussionmentioning
confidence: 99%